PELATIHAN TABLIGH BAGI SANTRI DALAM UPAYA KADERISASI DA’I TABLIGH TRAINING FOR SANTRI IN AN EFFORT TO REGENERATE DA’I - Muhammad Fauzi Arif; Hendi Suhendi; Malki Ahmad Nasir (HIKMAH : Jurnal Dakwah dan Sosial, 2021)
The cadre of da’i is the process of fostering prospective da’i through educational and training activities so that they have the ability to convey Islamic teachings well in Islamic society, the goal is that da'wah can take place from one generation to the next. One form of the da’i cadre process is tabligh training. This research is a follow-up to the Community Partnership Program (PKM) of the Da'wah Faculty of the Islamic University of Bandung at the Nurul Huda Islamic Boarding School Kaimas Garut. The aims of this research are; 1) to determine the planning of da’i cadre through tabligh training activities, 2) the form of tabligh training implementation, 2) evaluation of tabligh training activities. This research method uses a qualitative research type with a descriptive approach, while the research data is obtained through interviews with boarding school caregivers, and observations in tabligh training activities for students. The results showed that the planning of tabligh training activities started from cooperating with external parties to identify the tabligh abilities of the santri. The implementation of tabligh training activities includes three ways; 1) training in writing sermon texts and lectures, 2) training in da'wah rhetoric, 3) fostering the use of social media as a medium for da'wah. Evaluation of tabligh training activities for students is carried out through mentoring muhadhoroh activities. Kaderisasi da’i merupakan proses pembinaan calon-calon da’i melalui kegiatan pendidikan maupun pelatihan agar memiliki kemampuan menyampaikan ajaran Islam dengan baik di masyarakat Islam, tujuannya agar dakwah dapat berlangsung dari satu generasi ke generasi berikutnya. Salah satu bentuk proses kaderisasi da’i yaitu pelatihan tabligh. Penelitian ini merupakan tindak lanjut kegiatan Program Kemitraan Masyarakat (PKM) Fakultas Dakwah Universitas Islam Bandung di Pondok Pesantren Nurul Huda Kaimas Garut. Tujuan penilitian ini adalah ; 1) Untuk mengetahui perencanaan kaderisasi da’i melalui kegiatan pelatihan tabligh, 2) bentuk pelaksanaan pelatihan tabligh, 3) evaluasi kegiatan pelatihan tabligh. Metode penelitian ini menggunakan jenis penelitian kualitatif dengan pendekatan deskriptif, adapun data penelitian di dapatkan melalui hasil wawancara dengan pengasuh pondok, dan observasi dalam kegiatan pelatihan tabligh bagi para santri. Hasil penelitian menunjukkan bahwa perencanaan kegiatan pelatihan tabligh dimulai dari menjalin kerjasama dengan pihak eksternal untuk mengidentifikasi kemampuan tabligh para santri. Adapun pelaksanaan kegiatan pelatihan tabligh meliputi tiga cara; 1) pelatihan menulis teks khutbah maupun ceramah, 2) pelatihan retorika dakwah, 3) pembinaan pemanfaatan media sosial sebagai media dakwah. Evaluasi kegiatan pelatihan tabligh bagi para santri dilakukan melalui pendampingan kegiatan muhadhoroh.